Thermal, mechanical and thermomechanical properties of tough electrospun poly(imide-co-benzoxazole) nanofiber belts. (23rd July 2015) - Jiang, Shaohua; Duan, Gaigai; Chen, Linlin; Hu, Xiaowu; Ding, Yichun; Jiang, Chengmin; Hou, Haoqing
Abstract : Electrospun PI- co -PBO nanofiber belts possessed superior thermomechanical properties. Abstract : Mechanically strong electrospun nanofibers at high temperature are highly desired in the aerospace industry, high temperature filtration and fire protection clothing. In the present work, highly tough poly(imide- co -benzoxazole) (PI- co -PBO) nanofiber belts with excellent thermal stability, mechanical properties and thermomechanical properties were produced from the highly viscous methoxy-containing polyamic acid (MeO-PAA) solution by electrospinning followed by thermal rearrangement. The chemical structures of the polymer nanofibers and the corresponding thermal rearrangement were confirmed by 1 H-NMR, FT-IR and TGA. The mechanical properties and thermomechanical properties were characterized by a tensile test and thermomechanical analysis (TMA). The aligned nanofiber belts heat-treated at 450 °C (ANF-450) had the highest tensile strength of 559 MPa, a modulus of 11.2 GPa and a toughness of 12.0 J g −1, respectively, which were much higher than those of the pure PBO films made by thermal rearrangement. The TMA test showed that the ANF-450 exhibited a high tensile strength retention of 90% and a modulus retention of 94% at a high temperature of 200 °C. These excellent thermomechanical properties make electrospun PI- co -PBO nanofibers promising candidates in high temperature areas.